2021
DOI: 10.1126/sciadv.abg7156
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with RBD-P2 and N protects against SARS-CoV-2 in nonhuman primates

Abstract: Since the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), various vaccines are being developed, with most vaccine candidates focusing on the viral spike protein. Here, we developed a previously unknown subunit vaccine comprising the receptor binding domain (RBD) of the spike protein fused with the tetanus toxoid epitope P2 (RBD-P2) and tested its efficacy in rodents and nonhuman primates (NHPs). We also investigated whether the SARS-CoV-2 nucleocapsid protein (N) could increase vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Taken together, our results support previous findings on the potential importance of the Nprotein for vaccine development [59]. Immunization with the N protein protects against SARS-CoV-2 in non-human primates [60] and mice [61]. Another advantage to considering the vaccine potential of the N protein is its sequence conservation between SARS-CoV-2 and SARS-CoV and MERS-CoV [62].…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, our results support previous findings on the potential importance of the Nprotein for vaccine development [59]. Immunization with the N protein protects against SARS-CoV-2 in non-human primates [60] and mice [61]. Another advantage to considering the vaccine potential of the N protein is its sequence conservation between SARS-CoV-2 and SARS-CoV and MERS-CoV [62].…”
Section: Discussionsupporting
confidence: 89%
“…Several recent studies highlight the benefits of N as a vaccine antigen in animal models [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Here we have demonstrated the ability of N protein to strongly stimulate T cell responses with a Th1 bias. Other studies have also reported Th1 biased T-cell responses in NHP and mice models upon immunization with S protein or a modified RBD protein in combination with N protein with no evidence of vaccine associated enhanced respiratory disease (VAERD) [29,30] .…”
Section: Discussionmentioning
confidence: 99%